Gambaran Disonansi Kognitif Pada Individu Yang Menjalani Hubungan Friends With Benefits (Fwb) - Choria Nur Stari; Dessi Christanti (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Friend With Benefits (FWB) relationship is a new label for relationships with the opposite sex. Individuals who are in FWB relationships in Indonesia can experience cognitive dissonance because it is not in line with the norms that apply in Indonesia. Cognitive dissonance is an imbalance that occurs because there are two opposing thoughts, causing psychological discomfort. This study aimed to determine the description of cognitive dissonance in individuals who are in FWB relationships. The approach in this research was qualitative phenomenology. The data collection method used semi-structured interview techniques. The data analysis technique used deductive thematic analysis. Three participants in this study were aged 18-25 years who were currently in or had previously been in a FWB relationship. The results of the study showed that there were three main themes, namely sources of cognitive dissonance, psychological discomfort, and strategies for overcoming cognitive dissonance. Sources of cognitive dissonance include religion, culture, parental teachings, and experiences of FWB. Psychological discomfort was felt by participants in the form of feelings of guilt/sin, anxiety and doubt. Strategies used by participants to reduce cognitive dissonance include justification, self-affirmation, avoidance, and stopping FWB.